Assessment of the solar energy development role as a tool for the energy transition in Russia - Liudmila V. Nefedova; Yulia Yu. Rafikova (RUDN Journal of Ecology and Life Safety, 2023)
Based on the characteristics of the current state of the use of renewable energy sources (RES) in the world and in Russia, the role of solar energy in solving one of the urgent problems of the development of modern society - energy transition to the use of low-carbon energy sources is considered. The volumes of electricity produced and the reduction of CO2 emissions at photovoltaic stations operating in the regions of Russia at the beginning of 2022 were evaluated and analyzed. The Republic of Kalmykia and Altai were singled out, which have the largest shares of solar electricity in the energy balances, 35.7 and 23.2%, respectively. The problems of assessing the natural resource risks of using solar resources in the Russian Federation in connection with the climatic zoning of the territory are considered. The authors propose a method for assessing the degree of risk of using solar resources based on calculating the characteristics of the variability of solar radiation on the earth’s surface, assessing and mapping the level of natural resource risks. The levels of resource risks in the development of solar energy for the Orenburg and Astrakhan regions, leaders in the development of solar energy in Russia, were assessed.